2005
DOI: 10.1111/j.1551-2916.2005.00787.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Partial Pressure on the Dielectric Properties and Microstructures of Cofired Base‐Metal‐Electrode Multilayer Ceramic Capacitors

Abstract: The dielectric properties, dopant distributions, and microstructures of BaTiO 3 -based multilayer ceramic capacitors (MLCCs) sintered in H 2 -N 2 -H 2 O atmospheres with P O 2 5 10 À7.5 Pa (BMX-7.5) and P O2 5 10 À9.5 Pa (BMX-9.5) were studied, and the effects of oxygen partial pressures were analyzed. Dielectric measurements showed that BMX-7.5 had a lower dielectric constant at temperatures above 201C, but a higher dielectric constant at temperatures below 101C when compared with BMX-9.5. The coexistence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…The two devices which benefit in particular are multilayer ceramic capacitors (MLCCs) 1 and multilayer ceramic actuators. 2 These devices, however, must be sintered in a reducing atmosphere to prevent oxidation of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…The two devices which benefit in particular are multilayer ceramic capacitors (MLCCs) 1 and multilayer ceramic actuators. 2 These devices, however, must be sintered in a reducing atmosphere to prevent oxidation of the electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…In the aforementioned two papers, it was shown that the permittivity and piezoelectric constant increase with decreasing average grain size and reach the maximum at about 1 μm. On the other hand, it has been shown that the electrical properties and microstructures of the BaTiO 3 ceramics depend on the oxygen partial pressure [8,9]. Although grain size and oxygen activity have been found to play a significant role in dielectric and piezoelectric behavior of BaTiO 3 ceramics, it is difficult to find the optimal conditions experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that perovskite PZT films can be directly deposited onto base www.elsevier.com/locate/ceramint Available online at www.sciencedirect.com Ceramics International 36 (2010) 583-587 metal Cu foils [14,15] for microelectromechanical systems (MEMs) application. The processing atmosphere should be controlled in an appropriate oxygen partial pressure window in order to avoid oxidation of base metals [12][13][14][15]. In this study, we demonstrated that perovskite (Na,K)NbO 3 -based (NKN) piezoceramics can also be cofired with base metal Cu in a protective atmosphere.…”
Section: Introductionmentioning
confidence: 94%
“…Base metal electrode (BME) has become a hot issue for a long time [11]. The Ni electrode is commonly cofired with BaTiO 3 -based dielectrics to produce BME MLCCs [12,13]. It is also reported that perovskite PZT films can be directly deposited onto base www.elsevier.com/locate/ceramint Available online at www.sciencedirect.com Ceramics International 36 (2010) 583-587 metal Cu foils [14,15] for microelectromechanical systems (MEMs) application.…”
Section: Introductionmentioning
confidence: 98%